2020
DOI: 10.1186/s12967-020-02460-3
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical characterization, genetic profiling, and immune infiltration of TOX in diffuse gliomas

Abstract: Background Immunotherapies targeting glioblastoma (GBM) have led to significant improvements in patient outcomes. TOX is closely associated with the immune environment surrounding tumors, but its role in gliomas is not fully understood. Methods Using data from The Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA), we analyzed the transcriptomes of 1691 WHO grade I-IV human glioma samples. The R language was used to perform most of the statistical analyses. Somatic mutations and somatic co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…2 B). Given that immune checkpoint molecules were critical in regulating tumor immunity [28] , [51] , we then compared the levels of several series of immune checkpoint molecules related to antigen presentation, cell surface receptor, coinhibition, ligand and cell adhesion between the two clusters. Immune checkpoint markers tended to be overexpressed in cluster 1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 B). Given that immune checkpoint molecules were critical in regulating tumor immunity [28] , [51] , we then compared the levels of several series of immune checkpoint molecules related to antigen presentation, cell surface receptor, coinhibition, ligand and cell adhesion between the two clusters. Immune checkpoint markers tended to be overexpressed in cluster 1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immune checkpoint blockage (ICB) therapy targeting immune checkpoint molecules have demonstrated remarkable benefits (45). The significant correlation between ICP score and classical immune checkpoint molecules such as PDCD1, CD274, TIGIT, and LAG3 suggested that ICP score could be an effective indicator for immune checkpoint blockage (ICB) therapy (46)(47)(48)(49). Moreover, high ICP score prominently participated in the regulation of immunomodulators for tumor immunogenicity and antigen presentation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…System. Differential expressional genes (909 DEGs in total; the screen criteria was 0.677, which was automatically calculated by considering the mean and standard deviation of logFC) between clusters 1 and 2 were identified with P packages "limma" [29,30]. log FC ďż˝ mean(|log FC|) + 2 * sd(|log FC).…”
Section: Construction Of the Scoringmentioning
confidence: 99%